Large-scale assessment of aortic stenosis: facing the next cardiac epidemic?. (28th September 2017) - Ramos, Javier; Monteagudo, Juan Manuel; González-Alujas, Teresa; Fuentes, María Eugenia; Sitges, Marta; Peña, María Luisa; Carrasco-Chinchilla, Fernando; Echeverría, Tomás; Bouzas, Alberto; Forteza Alberti, José Francisco; Mesa, Dolores; De La Hera, Jesús María; et al.
Abstract: Aims: Aortic stenosis (AS) is the most frequent valvular disease in developed countries. As society grows older, the prevalence of AS increases. However, the real burden, current aetiology, severity distribution, and echocardiographic patterns of AS are not fully clear. The aim of the present study is to provide an accurate overall picture of AS, focusing on its epidemiology, aetiology, and echocardiographic features. Methods and results: A total of 29 502 consecutive echocardiograpies were prospectively included in this multicentre study. The present sample was composed of patients with advanced age (mean 75.2 years) and similar gender distribution. High proportion (7.2%) showed any grade of AS, with important number of patients (2.8%) presenting severe AS, most of them aged 75 years or more. Coexisting valvular disease appeared in almost half of the sample (49.6%), being the most frequently diagnosed aortic regurgitation (AR) (22%) followed by mitral regurgitation (MR) (15.6%). Degenerative aetiology was found in the vast majority (93.4%) of the studies whereas rheumatic is currently infrequent (3.35%). Low flow-low gradient (LFLG) appeared in 24.6% of patients with severe AS. Atrial fibrillation (23.1% vs. 11.6%; P = 0.002), MR (23.3% vs. 15.1%; P = 0.018), and right ventricle dysfunction (13.3% vs. 5.2%; P = 0.003) appeared frequently in LFLG group. Conclusions: Burden of AS is higher than previously assumed. Degenerative aetiology is the main cause of AS. Most of the patients are elder with high prevalence of significant co-existing valvular disease. LFLG severe AS is present in an important proportion of patients, showing high grade of left ventricle remodelling.